THINKING IN JAZZ: THE INFINITE ART OF IMPROVISATION, by Paul Berliner, Chicago Studies in Ethnomusicology, University of Chicago Press, 1994, pp. 883 (music texts 250pp) - Van Heerden, Rick (International Library of African Music, 1999)
pages: 191-193
Keywords: African Music